Plasma cystathionine and risk of acute myocardial infarction among patients with coronary heart disease: Results from two independent cohorts. (1st September 2018) - Dhar, Indu; Svingen, Gard F.T.; Pedersen, Eva R.; DeRatt, Barbara; Ulvik, Arve; Strand, Elin; Ueland, Per M.; Bønaa, Kaare H.; Gregory, Jesse F.; Nygård, Ottar K.
Abstract: Background: Cystathionine is a thio-ether and a metabolite formed from homocysteine during transsulfuration. Elevated plasma cystathionine levels are reported in patients with cardiovascular disease; however prospective relationships with acute myocardial infarction (AMI) are unknown. We investigated associations between plasma cystathionine and AMI among patients with suspected and/or verified coronary heart disease (CHD). Methods: Subjects from two independent cohort studies, the Western Norway Coronary Angiography Cohort (WECAC) (3033 patients with stable angina pectoris; 263 events within 4.8 years of median follow-up) and the Norwegian Vitamin Trial (NORVIT) (3670 patients with AMI; 683 events within 3.2 years of median follow-up) were included. Results: In both cohorts, plasma cystathionine was associated with several traditional CHD risk factors ( P < 0.001). Comparing the cystathionine quartile 4 to 1, age and gender adjusted hazard ratios (95% confidence intervals) for AMI were 2.08 (1.43–3.03) and 1.41 (1.12–1.76) in WECAC and NORVIT, respectively. Additional adjustment for traditional risk factors slightly attenuated the risk estimates, which were generally stronger in both cohorts among non-smokers, patients with higher age, and lower BMI or PLP status (P-interaction ≤ 0.04). Risk associations also tended to be stronger in patients not treated with B-vitamins. Additionally, in a subset of 80 WECAC patients, plasma cystathionine associated strongly negatively with glutathione, an important antioxidant and positively with lanthionine, a marker of H2 S production ( P < 0.001). Conclusions: Plasma cystathionine is associated with increased risk of AMI among patients with either suspected or verified coronary heart disease, and is possibly related to altered redox homeostasis. Highlights: Elevated systemic cystathionine levels have been observed in patients with cardiovascular diseases We assessed circulating cystathionine levels in patients with suspected or verified coronary heart disease (CHD) Plasma cystathionine was associated with increased risk for acute myocardial infarction Risk associations tended to be stronger in patients not treated with B-vitamins, and was modified by several CHD risk factors